Breeding phenology of Common Redstart (Phoenicurus phoenicurus) and its reproduction biology with artificial nests in Northeastern Ukraine - Yarys Olena (Sciendo, 2021)
The paper describes investigations on the reproduction biology (nesting, clutching, hatching, fledglings` departure) of the Common Redstart (Phoenicurus phoenicurus) in artificial nest boxes (AN) in Northeastern Ukraine. There were three sites of research: Hetman NNP, NPP “Gomilshansky Forests”, and RLP “Feldman Ecopark”. The research was performed during the nesting period from the first week of April to the first week of July in 2015‒2020. Annually, 5‒8 bird counts were conducted at each site. The first complete egg clutches at Hetman NNP were observed from 08.05 to 17.05 (2015‒2020) and at NPP “Gomilshansky Forests” from 02.05 to28.05 (2017‒2020). Dates of the first egg laying, at various conditions, had inter-annual variability because of unstable weather conditions in May. The average parameters of nests in AN at Hetman NNP were the following: diameter of nests (D) ‒ 124.1±6.3 mm; diameter of trays (d) ‒ 61.5±1.7 mm; nest height (H) ‒ 63.5±9.4 mm; depth of trays (h) ‒ 48.6±2.7 mm; nest mass (m) ‒ 43.7±3.8 mm. The size of complete clutches in Northeastern Ukraine was calculated when eggs were incubated. According to the average indicators, during 2015‒2020, the average size of the clutch was 6.9±0.3 (5‒8) eggs at Hetman NNP, 6.2±0.4 (6‒8) eggs at NPP “Gomilshansky Forests” and 8.5±0.5 (8‒9) eggs at RLP “Feldman Ecopark”. Incubation period of Ph. phoenicurus lasted on average for 15‒20 days.